Antimicrobial activity of a cationic guanidine compound against two pathogenic oral bacteria - Escamilla García, Erandi; Alcázar Pizaña, Andrea Guadalupe; Segoviano Ramírez, Juan Carlos; Del Angel Mosqueda, Casiano; López Lozano, Ada Pricila; Cárdenas Estrada, Eloy; De la Garza Ramos, Myriam Angélica; Medina de la Garza, Carlos Eduardo; Márquez, M. (Hindawi Pub. Corp., 2017)
This study evaluated the potential antimicrobial properties of a polyguanidine (CatDex) on two oral bacteria. Chlorhexidine gluconate 1340